HEGEMONIA E CONTRA-HEGEMONIA NA CULTURA POPULAR DO MARANHÃO - Letícia Conceição Martins Cardoso (Revista de Políticas Públicas, 2018)
The paper is about the complex interactions and borrowings between popular and hegemonic cultures, taking as an example the practice of Bumba meu boi in Maranhão. It is no longer possible to think about the relationship between different cultures, identities and social movements from a bipolar and rigid confrontation between elites and subaltern classes. In practice, there is a game of exchanges and disputes between them, in which communication plays an important role in the development of strategies and tactics by the subjects. So, the work aims to understand how Bumba meu boi, coming from the popular and peripheral layers, has been interacting with local hegemonic political power and often assuming a counter-hegemonic position. For a Gramscian bias, the analysis is executed from data collected in observations and from interviews with “players” of Bumba meu boi in São Luís - MA.